AI for emerging verticals : human-robot computing, sensing and networking - Shakir, Muhammad Zeeshan; Ramzan, Naeem (Institution of Engineering and Technology, 2020)
The book comprises 17 chapters dealing with the following subjects: human-robot computing, sensing and networking; deep learning techniques; human manipulation modelling; autonomous robotic grasping; soft end-effectors; artificial intelligence; affective computing; emotion recognition; machine learning-based affect detection; human-horse interaction; robot intelligence; visual object tracking by quadrotor; artificial neural networks; fuzzy logic controller; predictive mobility management in cellular networks; data analytics; 5G and beyond-5G wireless networks; deep Q-network-based coverage hole detection; localization of ultrawide bandwidth sensor nodes; cascaded machine learning; indoor classification and localization; adaptive feature selection; EEG-based biometrics; template ageing; perceptual video quality metrics; multitask learning for autonomous driving; machine-learning-enabled ECG monitoring; early hyperkalaemia detection; deterministic compressed sensing; data reduction; connected health; large-scale distributed and scalable SOM-based architecture; surface water pollution monitoring; and Internet of Things
Keywords: Cell phone systems.; Clinical medicine -- Computer programs.; Detectors.; elektronické knihy; electronic books